2017
DOI: 10.1002/aic.16016
|View full text |Cite
|
Sign up to set email alerts
|

3D‐foam‐structured nitrogen‐doped graphene‐Ni catalyst for highly efficient nitrobenzene reduction

Abstract: We report the preparation of a porous 3D‐foam‐structured nitrogen‐doped graphene‐Ni (NG/NF) catalyst and the evaluation of its performance in the reduction of nitrobenzene (NB) through detailed studies of the kinetics. The NG/NF catalyst showed a significantly higher reaction rate than pure Ni foam (NF). Moreover, the separation of the 3D‐foam‐structured catalyst from the products was more convenient than that of NG powdered catalysts. The obtained kinetics data fit well to the Langmuir‐Hinshelwood model, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…CV tests were performed over the potential window from −1.0 to 1.0 V. The data for N-RGO-5 (figure 8(a)) show a good approximately rectangular shape. There is no obvious peak tip compared with the trends for the other samples, indicating that N-RGO-5 exhibited the properties of an ideal double-layer capacitor [43]. N-RGO-5 exhibited the largest specific capacitance among the examined samples, as shown by the large area under the current-voltage curve.…”
Section: Electrochemical Measurementsmentioning
confidence: 86%
“…CV tests were performed over the potential window from −1.0 to 1.0 V. The data for N-RGO-5 (figure 8(a)) show a good approximately rectangular shape. There is no obvious peak tip compared with the trends for the other samples, indicating that N-RGO-5 exhibited the properties of an ideal double-layer capacitor [43]. N-RGO-5 exhibited the largest specific capacitance among the examined samples, as shown by the large area under the current-voltage curve.…”
Section: Electrochemical Measurementsmentioning
confidence: 86%
“…Single non-noble-metal catalysts often lack catalytic activity due to their tightly stacked structure and inactivity. Many studies have shown that loading non-noble metals on a specific carrier to increase the surface exposure can improve the catalytic activity for 4-NP reduction to some extent. , Conventional strategies for loading non-noble-metal nanoparticles (nNMNPs) onto a support (metal–organic framework, covalent organic frameworks, graphene support, etc.) are often based on physical pre-preparing loading.…”
Section: Introductionmentioning
confidence: 99%
“…根据不同的模型选择以及理论计算, 发现带负 [39] 前期研究发现使用镍泡沫的旋转泡沫反应器与金属 丝网结构相比, 可以将微观混合时间缩短30%, 极大 强化液固相传质. 在此基础上, 本课题组 [40] [40] Figure 5 (Color online) NG/NF catalyst. (a) UV/Vis spectra of the reaction solution during catalysis by NG/NF; (b) catalyst recycling performance; (c), (d) schematic diagram of L-H model [40] 表 1 非金属碳基材料在液相催化反应中的应用 2.2 工业气相催化反应 工业生产中的气相催化反应大多数都需要在高 温高压下进行 [41] , 多年来德国马普学会Fritz-Harber 研 究 所 、 中 国 科 学 院 沈 阳 金 属 研 究 所 苏 党 生 课 题 组 [42] 围绕非金属碳基纳米催化材料在气相氧化脱氢 反应体系的应用开展了系列研究.…”
unclassified